Transformation of the phytopathogenic fungus Sclerotium cepivorum Berk using protoplasts fusion - Acosta-García Gerardo; Pantoja-Hernández Miguel Ángel; Muñoz-Sánchez Claudia Ivonne; Pérez-Pérez Cristina; Guevara-González Ramón Gerardo; Torres-Pacheco, Irineo; Delgadillo-Sánchez Felipe; González-Chavira Mario Martín; Guevara-Olvera, Lorenzo (Revista Mexicana de Ciencias Agrícolas, 2018)
White rot, a disease of most concern to the producers of garlic (Allium sativum), is caused by the phytopathogenic fungus Sclerotium cepivorum Berk. In order to develop procedures of molecular biology to the fungus, in this paper we describe a transformation method using fusion of protoplasts in the presence of polyethylene glycol 3350 (PEG). We used the plasmid pAN7-1 which confers resistance to hygromycin B, which contains the hygromycin phosphotransferase gene B (hph) from Escherichia coli under the glyceraldehyde phosphate dehydrogenase promoter (GPDA) and the anthranilate synthase terminator (trpC) of the filamentous fungus Aspergillus nidulans. The recovered transformants in the regeneration medium potato dextrose agar-sorbitol (PDA-S) in the presence of 200 μgmL -1 of hygromycin B were analyzed by amplifying a fragment of the bacterial gene hph by PCR with specific oligonucleotides: Hig 1, Sentido 5’ GAC CTG CTG AGG TCC CTC 3 ́ and Hig 2, antisentido 5’ GCC CTC GGA CGA GTG CTG 3 ́. Obtaining 12-18 frequencies of transformants of S. cepivorum per μg of vector DNA. The results described in this paper will contribute to the molecular characterization of the genes involved in the phenomenon of pathogenesis of S. cepivorum on garlic.